Feature Compression Applications of Genetic Algorithm - Zou, Meiling; Jiang, Sirong; Wang, Fang; Zhao, Long; Zhang, Chenji; Bao, Yuting; Chen, Yonghao; Xia, Zhiqiang (Frontiers in Genetics, 2022)
With the rapid development of molecular breeding technology and many new varieties breeding, a method is urgently needed to identify different varieties accurately and quickly. Using this method can not only help farmers feel convenient and efficient in the normal cultivation and breeding process but also protect the interests of breeders, producers and users. In this study, single nucleotide polymorphism (SNP) data of 533 Oryza sativa, 284 Solanum tuberosum and 247 Sus scrofa and 544 Manihot esculenta Crantz were used. The original SNPs were filtered and screened to remove the SNPs with deletion number more than 1% or the homozygous genotype 0/0 and 1/1 number less than 2. The correlation between SNPs were calculated, and the two adjacent SNPs with correlation R2>0.95 were retained. The genetic algorithm program was developed to convert the genotype format and randomly combine SNPs to calculate a set of a small number of SNPs which could distinguish all varieties in different species as fingerprint data, using Matlab platform. The successful construction of three sets of fingerprints showed that the method developed in this study was effective in animals and plants. The population structure analysis showed that the genetic algorithm could effectively obtain the core SNPs for constructing fingerprints, and the fingerprint was practical and effective. At present, the two-dimensional code of Manihot esculenta Crantz fingerprint obtained by this method has been applied to field planting. This study provides a novel idea for the Oryza sativa, Solanum tuberosum, Sus scrofa and Manihot esculenta Crantz identification of various species, lays foundation for the cultivation and identification of new varieties, and provides theoretical significance for many other species fingerprints construction.